2014
DOI: 10.3109/15376516.2014.948248
|View full text |Cite
|
Sign up to set email alerts
|

Renal tight junction proteins are decreased in cisplatin-induced nephrotoxicity in rats

Abstract: CP altered the TJ proteins expression and localization in the proximal tubule that was associated with oxidative/nitrosative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
1
20
1
Order By: Relevance
“…Claudin 2 expression is regulated by components of the immune system (including IL-2, tumour necrosis factor (TNF), IL-13, IL-15, and IL-17) and growth factor signalling (including pro-epidermal growth factor (EGF), hepatocyte growth factor (HGF), extracellular signal-regulated kinase 1 (ERK1; also known as MAPK3), ERK2, and the RACα serine/threonine-protein kinase (AKT) pathways) 54 . Under pathophysiological conditions such as cisplatin-induced nephrotoxicity, ischaemic injury, or metabolic acidosis, claudin 2 expression is reduced, resulting in impaired paracellular transport of cations, which may contribute to disruption of the proximal tubule epithelium 55,56 . Tight junction injury can be visualized in vitro by tracking immunofluorescence or leakage of labelled inulin.…”
Section: Characterization Of Cellular Modelsmentioning
confidence: 99%
“…Claudin 2 expression is regulated by components of the immune system (including IL-2, tumour necrosis factor (TNF), IL-13, IL-15, and IL-17) and growth factor signalling (including pro-epidermal growth factor (EGF), hepatocyte growth factor (HGF), extracellular signal-regulated kinase 1 (ERK1; also known as MAPK3), ERK2, and the RACα serine/threonine-protein kinase (AKT) pathways) 54 . Under pathophysiological conditions such as cisplatin-induced nephrotoxicity, ischaemic injury, or metabolic acidosis, claudin 2 expression is reduced, resulting in impaired paracellular transport of cations, which may contribute to disruption of the proximal tubule epithelium 55,56 . Tight junction injury can be visualized in vitro by tracking immunofluorescence or leakage of labelled inulin.…”
Section: Characterization Of Cellular Modelsmentioning
confidence: 99%
“…BUN, plasma creatinine, N-acetyl-β-D-glucosaminidase (NAG), NGAL, KIM-1 were used as markers of renal injury 32,48 . BUN and plasma creatinine were determined with commercial kits from Spinreact® 49 .…”
Section: Determination Of Renal Functionmentioning
confidence: 99%
“…We previously reported that occludin and claudin-2 expressions are decreased in CISinduced nephrotoxicity associated with oxidative stress derived in part to an increased production of superoxide anion (O 2 •-) by nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activity 32,40 . The potential effect of curcumin against TGFβ1-induced EMT and fibrosis, and alterations in TJ and AJ structure and function has not been evaluated in CIS-induced nephrotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 There are many molecular mechanisms associated with long-term nephrotoxicity induced by cisplatin, including oxidative stress and TJ protein expression changes, apoptosis, inflammation, and fibrogenesis. [10][11][12] Among these nephrotoxic mechanisms, the loss of F-actin stress fibers is known to be an early step of cisplatin-mediated nephrotoxicity, which leads to cell detachment. 13,14 In addition, after injury or renal tubular cell differentiation, several markers have been reported to increase their concentration: podocalyxin (a podocyte marker), multidrug and toxin extrusion proteins 1 and 2 (MATE; responsible for cisplatin excretion into urine), organic cation and organic anion transporters (OCT and OAT, responsible for the accumulation of cisplatin from the blood into proximal tubules), and kidney injury molecule-1 (KIM-1, transmembrane protein).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the techniques used to detect cellular damage in nephrotoxic events involve imaging approaches for visualizing expression of cell markers, cell viability, apoptosis assays, quantitative reverse transcription-PCR, and omics approaches. 12,29 Although these methods provide information about the mechanisms of toxicity of the drugs, they are time-consuming, require the use of chromophores or fluorophores, and, most importantly, are usually limited to providing ''end-point'' data rather than real-time monitoring. An emerging trend in the field of in vitro toxicology is to use electronic impedance spectroscopy (EIS) for monitoring cells.…”
Section: Introductionmentioning
confidence: 99%